Next-Generation Composite Coating System: Nanocoating - Bao, Weiwei; Deng, Zhifeng; Zhang, Shaodan; Ji, Zhuoting; Zhang, Haichang (Frontiers in Materials, 2019)
Nanocoating combines the protective properties of conventional coating system with effects on nanoscale such as high hardness, UV scattering, and uniform dispersing. Their facile and low-cost synthesis, together with superior protective properties and multi-functionalities, makes nanocoating attractive candidates for next-generation coating systems. In this review, a brief introduction regarding mainstream nanocoating and its related challenges including the zinc oxide-, titanium dioxide-, silica dioxide-, graphene-, carbon nanotube-based nanocoating system is presented. Finally, a perspective of the nanocoating is demonstrated.